Canonical narrative schema : a key to understanding the victory discourse in Judith : a Greimassian contribution - Hobyane, Risimati S. (Journal for semitics, 2015)
A historical critical approach to narratives has contributed significantly to the analysis of ancient narratives. However, this approach has somehow unfairly ignored some other critical aspects of many ancient narratives. Judith is no exception to this claim. While appreciating the contribution of historical critical approaches to Judith (i.e., the questions on authorship, historical and geographical inconsistencies etc.), the aim of this article is to go beyond the historicity of Judith, and reveal some narrative techniques employed by the author in creating a woman protagonist who is destined to achieve the unthinkable in the minds of the men of her contemporary world. This article explores these narrative techniques by employing the narrative analysis, narrative syntax in particular, of the Greimassian approach to narrative texts. Subsequently, this article contributes to research of Judith by revealing the path that Judith followed on her quest to save the Jewish religion from extinction during the Second Temple period.